Enhancement of gel properties of Scomberomorus niphonius myofibrillar protein using phlorotannin extracts under UVA irradiation. Issue 7 (22nd June 2020) - Jiang, Di; Shen, Ping; Pu, Yuan; Jin, Meiran; Yu, Chenxu; Qi, Hang
Abstract : Abstract: The effect of phlorotannin extracts (PTE) (from sporophyll of Undaria pinnatifida ) added at different levels (0, 25, 125, 625 µmol/g protein) on the gel properties of mackerel ( Scomberomorus niphonius ) myofibrillar protein (MP) was studied with and without ultraviolet A (UVA) irradiation. The results showed that the gel strength and cooking yield increased in a PTE dose‐dependent manner, and at the level of 625 µmol/g protein PTE, the highest gel strength of 308.43 ± 8.12 (mN·cm) and cooking yield of 76.16 ± 1.40% were obtained in the samples treated with UVA irradiation. The same samples also showed increased carbonyl content, decreased total sulfhydryl, unwinding of α‐helix, and quenching of fluorescence intensity of endogenous tryptophan, all of which indicated that elevated protein oxidation in these samples led to enhanced protein cross‐linking. Results of sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS‐PAGE) indicated aggregation of myosin heavy chains (MHCs) in the UVA‐treated gels with PTE, also evidenced by the dense three‐dimensional network structure in these samples visualized by scanning electron microscopy (SEM). Electron spin resonance (ESR) and spin trapping results indicated that free radicals were produced during the gelation process, possibly originated from UVA‐treated PTE, which played a critical role of oxidizing fish MPs, and eventually led to the improvement of the textural properties of the mackerel MP gel. Practical Application: Brown algae are a family of high‐yield marine algae. Phlorotannin extracts are highly active natural substances extracted from brown algae that can have many applications. Ultraviolet A (UVA) as a green and environmentally friendly physical processing method has been widely used in food processing in recent years. The method proposed in this study could be utilized to improve properties of fish protein gel made from poorly performing low‐priced fishes, and provide workable guidance for industry to expand the application of brown algae in food processing to better meet consumer's demand for high‐quality marine foods.